DROUGHT MAPPING USING STANDARDIZED PRECIPITATION INDEX (SPI) CIUJUNG WATERSHED INDONESIA - Wigati, Restu; Fathonah, Woelandari; Putu Purnaditya, Ngakan; Mina, Enden; Susilawati (POLITEKNIK NEGERI JAKARTA, 2025)
Reduced rainfall characterizes drought compared to the usual levels and persists for over a season. Drought is crucial in exacerbating water scarcity, hindering its ability to meet fundamental needs. It remains a persistent issue in various regions of Indonesia, including the Ciujung watershed. The primary objective of this study is to assess the spatial and temporal distribution of drought using SPI-based drought index maps in the Ciujung watershed. One method for determining drought severity in each area is employing the Standardized Precipitation Index (SPI). Rainfall data spanning the past 22 years, collected by 10 rain gauge stations, were analyzed using the ArcGIS application to generate drought maps. SPI analysis yields drought indices for various short-term periods, such as 3-month SPI, 6-month SPI, 9-month SPI, and 12-month SPI. The most prolonged drought period was documented at the Ciboleger rain station, extending over 48 months. In contrast, the most severe drought was recorded at the Bojongmanik rain station in Lebak Regency, with a value of -3.46. This research underscores the effectiveness of short-term SPI measurement in providing more detailed insight into drought conditions, emphasizing the significance of immediate preventive measures in regions experiencing the most severe drought conditions.